Determination of the upper limit of monoglyceride content in biodiesel for B30 implementation based on the measurement of the precipitate in a Biodiesel–Petrodiesel fuel blend (BXX). (15th December 2019) - Paryanto, Imam; Prakoso, Tirto; Suyono, Eko Agus; Gozan, Misri
Abstract: Biodiesel, in the form of a blended fuel (BXX) with 20%-vol biodiesel (B20), has been on sale on the Indonesian market since early 2016. There is a plan to increase its percentage by up to 30% by 2020, as stated in the biodiesel mandatory phase implementation report. One of the important parameters in biodiesel quality for the implementation of higher biodiesel percentage is monoglyceride content. Monoglyceride presence in biodiesel is caused by the incomplete conversion of raw material oils during the transesterification process, with alcohol, and it remains in the biodiesel product. The presence of monoglyceride in BXX fuel, especially at low-temperature conditions, can cause the formation of a precipitate that accelerates fuel filter clogging. The monoglyceride impurities, even in very low amounts, can trigger the formation of a precipitate. The amount of precipitate is an important factor that can affect the time taken before the fuel filter becomes blocked. The determination of the newly proposed upper limit of monoglyceride content parameter in biodiesel standard is necessary for B30 implementation so the potential amount of monoglyceride precipitate can be anticipated. The limit was proposed to be determined by benchmarking the amount of precipitate formed in B20 or B10 at various temperature conditions. The research was carried out by applying a modified cold soak filtration test method of ASTM D7501 for the precipitation test. Monopalmitin was added to biodiesel with low monoglyceride content to vary monoglyceride content so that each sample had approximate monoglyceride contents of 0.17%, 0.2%, 0.4%, 0.6% and 0.8%. Each biodiesel sample was then blended with petroleum diesel fuel to produce B10, B20 and B30. Each 100 ml sample was separately soaked in the cooling chamber at constant temperature conditions of 15 °C, 20 °C and 25 °C and at a room temperature condition for 21 days. Each sample was then filtered, washed with petro-ether, vacuum-dried and weighed for a constant amount of precipitate retained on the filter. The proposed upper limits of monoglyceride content in biodiesel for B30 with respect to the same amount of precipitate at each corresponding temperature condition in B20 and B10 were found to be 0.62% and 0.50%, respectively. However, with respect to the same amount of precipitate at room temperature in B20, the proposed upper limit of monoglyceride content in biodiesel for B30 was found to be in the range of 0.40–0.62%, while in the range of 0.33–0.51% for B10. From these results, the upper limit of monoglyceride content in biodiesel for B30 implementation should be lower than the current standard limit to achieve the same quality as biodiesel for B20 use.